2011
DOI: 10.1007/s10571-011-9693-2
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in Phenylketonuria: What is the Evidence?

Abstract: Phenylketonuria (PKU) is an inborn error of amino acid metabolism caused by severe deficiency of phenylalanine hydroxylase activity, leading to the accumulation of phenylalanine and its metabolites in blood and tissues of affected patients. Phenylketonuric patients present as the major clinical feature mental retardation, whose pathomechanisms are poorly understood. In recent years, mounting evidence has emerged indicating that oxidative stress is possibly involved in the pathology of PKU. This article address… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
50
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 126 publications
4
50
0
1
Order By: Relevance
“…However, the GPx activity level expresses a tight negative connection with the serum Phe level, suggesting that Phe per Se inhibits GPx activity [32]. Recent clinical and experimental studies suggest that Phe evince oxidative stress in the hippocampus and cerebral cortex of developing rats [33].…”
Section: Discussionmentioning
confidence: 99%
“…However, the GPx activity level expresses a tight negative connection with the serum Phe level, suggesting that Phe per Se inhibits GPx activity [32]. Recent clinical and experimental studies suggest that Phe evince oxidative stress in the hippocampus and cerebral cortex of developing rats [33].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the PAH system suffers from a constant shortage of BH 4 . Oxidative stress35 or other environmental factors with negative impact on BH 4 availability may trigger PAH deficiency and thus may further aggravate clinical phenotypes. Taken together, alterations in BH 4 demand may add to the molecular mechanisms underlying phenotypic variability related to both disease severity and BH 4 responsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Our results in this study are also in agreement with the data reported by Mc Guire et al (2009), showing a marked reduction of urinary AOx in patients with PA. Interestingly, we found that patients under therapy also presented deficiency of their urinary AOx. It is presumed that these alterations can occur because of the treatment with restricted diets (such as in phenylketonuric patients) which are poor in micronutrients necessary for the antioxidant status or, alternatively, by an unusual increase in metabolic by-products which will directly or indirectly deplete the cell's antioxidant capacity (Moyano et al 1997;Wajner et al 2004;Sitta et al 2011;Ribas et al 2011).…”
Section: Discussionmentioning
confidence: 99%